2020
DOI: 10.3390/jcm9123949
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Suboptimal Peak Inspiratory Flow in Patients with Stable COPD

Abstract: Objective: Although the importance of assessing inspiratory flow in the selection of treatments for chronic obstructive pulmonary disease (COPD) is understood, evaluation of this factor is not yet widespread or standardized. The objective of the present work was to evaluate the peak inspiratory flow (PIF) of patients with COPD and to explore the variables associated with a suboptimal PIF. Methods: An observational, cross-sectional study was carried out at specialized nursing consultations over a period of 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 37 publications
1
36
0
5
Order By: Relevance
“…This supports previous studies which have shown that female patients and older patients tend to have lower PIF. [7][8][9] Additionally, we noted a higher proportion of tall participants (>180 cm) in the PIF ≥60 L/min cohort than the PIF <60 L/min cohort, in line with previous studies that suggest an association between height and PIF. 8,34 Of note, there were more patients with severe COPD, according to GOLD classification, or a lower percent predicted FEV 1 in the PIF <60 L/min cohort.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This supports previous studies which have shown that female patients and older patients tend to have lower PIF. [7][8][9] Additionally, we noted a higher proportion of tall participants (>180 cm) in the PIF ≥60 L/min cohort than the PIF <60 L/min cohort, in line with previous studies that suggest an association between height and PIF. 8,34 Of note, there were more patients with severe COPD, according to GOLD classification, or a lower percent predicted FEV 1 in the PIF <60 L/min cohort.…”
supporting
confidence: 92%
“…5,6 The delivery and deposition of medication in the lungs by these devices is affected by both inhaler characteristics and patient-related factors, such as peak inspiratory flow (PIF). 6,7 DPIs, for example, require a PIF of >60 L/minute (low to medium-high resistance devices) 6,[8][9][10] to overcome the inhaler's internal resistance and separate the medicine from its carrier particles. [11][12][13][14] Duarte et al reported that as many as one in five ambulatory patients with COPD have suboptimal PIF.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,12,[20][21][22][23][24]26,32,34,35, Reports of asthma studies (n = 30); review articles (n = 10); and non-English language articles, editorials, and articles involving healthy subjects or patients with other respiratory diseases; or reports from modeling/simulations (n = 48) were excluded. An additional seven articles were included from the authors' personal libraries; 33,[76][77][78][79][80][81] therefore, a total of 47 reports were included in the analysis.…”
Section: Pif In Published Studiesmentioning
confidence: 99%
“…Целый ряд исследований показал снижение эффективности порошковых ингаляторов у лиц с субоптимальным потоком на вдохе. В частности, у больных, не способных выполнить вдох с должным усилием, чаще отмечались обострения ХОБЛ [6,30,31].…”
Section: респимат и скорость инспираторного потокаunclassified
“…Проблема усугубляется тем, что врач, наблюдая за выполнением вдоха, не может распознать больных с субоптимальным потоком на вдохе, а приборы, позволяющие измерить объемную скорость при вдохе через ингалятор, пока недоступны в нашей стране [5]. Больные ХОБЛ с субоптималым потоком на вдохе достоверно чаще совершают технические ошибки во время ингаляции, обострения у этих больных отмечаются почти в два раза чаще по сравнению с больными с оптимальным потоком [6]. Обучение не способно обеспечить увеличение потока на вдохе [7], так как причинами сниженного потока являются высокая гиперинфляция и снижение усилия дыхательной мускулатуры [5].…”
Section: Introductionunclassified